Inhibition of ubiquitin‐specific protease 2 causes accumulation of reactive oxygen species, mitochondria dysfunction, and intracellular ATP decrement in C2C12 myoblasts. Issue 14 (28th July 2019) - Hashimoto, Mayuko; Saito, Natsuko; Ohta, Haru; Yamamoto, Kumiko; Tashiro, Asuka; Nakazawa, Kosuke; Inanami, Osamu; Kitamura, Hiroshi
Abstract: Ubiquitin‐specific protease 2 (USP2) is considered to participate in the differentiation of myoblasts to myotubes, however, its functions in myoblasts under growth conditions remain elusive. In this study, we analyzed the physiological roles of USP2 in myoblasts using Usp2 knockout (KO) C2C12 cells as well as a USP2 specific inhibitor. In addition to the disruption of differentiation, clustered regularly interspaced short palindromic repeats/Cas9‐generated Usp2 KO cells exhibited inhibition of proliferation compared to parental C2C12 cells. Usp2 KO cells reduced the accumulation of intracellular adenosine triphosphate (ATP) content and oxygen consumption. Moreover, Usp2 KO cells had fragmented mitochondria, suggesting that mitochondrial respiration was inactive. The deficiency of Usp2 did not affect the enzymatic activities of respiratory chain complexes I, III, IV, and V. However, mitochondrial membrane permeability—evaluated using calcein AM‐cobalt staining—was increased in Usp2 KO cells. The membrane potential of Usp2 KO cells was clearly decreased. Usp2 KO cells accumulated reactive oxygen species (ROS) in the mitochondria. The USP2‐selective inhibitor ML364 also increased the levels of mitochondrial ROS, and modulated the membrane potential and morphology of the mitochondria. These effects were followed by a decrement in the intracellular content of ATP. Based on these findings, we speculate that USP2 may be involved in maintaining the integrity of the mitochondrial membrane. This process ensures the supply of ATP in myoblasts, presumably leading to proliferation and differentiation. Abstract : We investigated the role of USP2 in myoblasts using a gene knockout cell model and specific inhibitor treatment. Our principle finding was that USP2 maintains oxidative phosphorylation in myoblasts. Although USP2 does not modulate the activities of mitochondrial complex enzymes, it markedly affects the mitochondrial membrane potential and membrane integrity, possibly through removal of reactive oxygen species.